2017
DOI: 10.1590/1807-1929/agriambi.v21n12p817-821
|View full text |Cite
|
Sign up to set email alerts
|

Spikelet sterility in rice genotypes affected by temperature at microsporogenesis

Abstract: A B S T R A C TThis study evaluated the effect of temperatures during the phase of microsporogenesis on spikelet sterility of paddy rice and identified genotypes tolerant to low temperatures at this growth stage. The inbreds SC681, SC491, and SC676 and the cultivars Epagri 109 and SCS116 Satoru were assessed. The genotypes were submitted for three days in a growth chamber to five temperatures at microsporogenesis: 9, 12, 15, 18, and 21 o C. For each tested temperature, a control was kept in the greenhouse unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 18 publications
1
5
0
8
Order By: Relevance
“…Regarding the range of spikelet sterility -from 4.0 and 84.1% ( Marschalek et al (2015Marschalek et al ( , 2017Marschalek et al ( and 2019 by Epagri indicate that these two lines usually show high yields, validating their adaptability for colder areas, i.e., under potential temperature stress. This may indicate the existence of a similar or overlapping tolerance mechanism to extreme temperatures in the reproductive period of the crop, regardless of whether it is high or low, as Jagadish et al (2010), Xiong (2013), andBaliuag et al (2015) reported.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the range of spikelet sterility -from 4.0 and 84.1% ( Marschalek et al (2015Marschalek et al ( , 2017Marschalek et al ( and 2019 by Epagri indicate that these two lines usually show high yields, validating their adaptability for colder areas, i.e., under potential temperature stress. This may indicate the existence of a similar or overlapping tolerance mechanism to extreme temperatures in the reproductive period of the crop, regardless of whether it is high or low, as Jagadish et al (2010), Xiong (2013), andBaliuag et al (2015) reported.…”
Section: Resultsmentioning
confidence: 99%
“…Esta característica é influenciada diretamente pelas temperaturas logo antes, durante e logo após a antese. Estas fases foram consideradas por AGUIAR et al (2013), BRITO et al (2017), SOUZA et al (2017e 2019, como as mais sensíveis do arroz irrigado, principalmente a temperaturas elevadas. Outro fator que pode contribuir para o aumento da esterilidade é a presença de doenças, como a Magnaporthe grisea, popularmente conhecida por brusone do pescoço.…”
Section: Resultsunclassified
“…Portanto, o aumento da esterilidade com o atraso da época de semeadura pode estar associado às altas temperaturas que ocorreram nos meses de janeiro e fevereiro (Figura 1). As temperaturas máximas registradas no período compreendido entre a microsporogênese e a floração estão diretamente ligadas à esterilidade de espiguetas (SOUZA et al 2017). Em nosso estudo, neste período, as temperaturas máximas para a primeira, segunda e terceira semeadura foram de, respectivamente, 32,3 °C, 29 °C e 31 °C.…”
Section: Resultsunclassified
“…A linhagem SC 676 foi a mais produtiva, no entanto não diferiu significativamente dos cultivares SCS122 Miura e SCS116 Satoru. Comportamento semelhante foi observado em trabalhos conduzidos sob baixas temperaturas por Marschalek et al (2015;2019), Souza (2015) e Souza et al (2017). As menores produtividades foram registradas nos cultivares Epagri 109 e SCS121 CL.…”
Section: Resultsunclassified